A proposed extension of the CODAM model for human attention - Neokleous, Kleanthis C.; Avraamides, Marios N.; Neocleous, Costas (My University, 2010)
A new computational model of visual attention is proposed on a theoretical basis, based on the CODAM model (Taylor, 2002, [25], 2006). Also a more general mechanism is proposed for an attention model of two or more senses working concurrently. The additional mechanism is mainly based on the interaction of the attention mechanism in the brain with working memory
Keywords: Neural networks (Computer science); Information systems; Management information systems; Attention